2023
DOI: 10.1186/s13071-023-05856-4
|View full text |Cite
|
Sign up to set email alerts
|

LILRB4 regulates the function of decidual MDSCs via the SHP-2/STAT6 pathway during Toxoplasma gondii infection

Abstract: Background Toxoplasma gondii infection can cause adverse pregnancy outcomes, such as recurrent abortion, fetal growth restriction and infants with malformations, among others. Decidual myeloid-derived suppressor cells (dMDSCs) are a novel immunosuppressive cell type at the fetal-maternal interface which play an important role in sustaining normal pregnancy that is related to their high expression of the inhibitory molecule leukocyte immunoglobulin-like receptor B4 (LILRB4). It has been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…LILRB4, also known as ILT3, is an essential immune checkpoint molecule that maintains immune homeostasis and modulates immune responses. LILRB4 is associated with several diseases, including cancer, autoimmune diseases, chronic inflammation, infectious diseases, and transplantation 27 31 . LILRB4 is highly expressed in acute myeloid leukemia and mediates T-cell suppression and infiltration 32 .…”
Section: Discussionmentioning
confidence: 99%
“…LILRB4, also known as ILT3, is an essential immune checkpoint molecule that maintains immune homeostasis and modulates immune responses. LILRB4 is associated with several diseases, including cancer, autoimmune diseases, chronic inflammation, infectious diseases, and transplantation 27 31 . LILRB4 is highly expressed in acute myeloid leukemia and mediates T-cell suppression and infiltration 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It could cause severe pregnancy complications, such as abortion, stillbirth, anencephaly, and congenital toxoplasmosis 1,2,47 . Our previous studies reported that the abnormal pregnant outcomes with T. gondii infection were due to the dysfunction of decidual immune cells resulted from the abnormal expression of functional membrane molecules and abnormal production of cytokines in dNK cells, dMDSCs, dMφ, dDCs and dTregs 3,4,5,6,48,49 . Recently, a novel decidual MDSCs have drawn increased attention due to their outstanding immune suppressive properties, which play an important role in sustaining human pregnancy 8.9 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proved that WT mice infected with T. gondii in early pregnancy can cause serious adverse pregnancy outcomes, which are caused by the dysfunction of immune cells, such as dMDSCs 48,49 , dNK cells 3,53 , dMφ 4,54 and dDCs 5,14 found that the depletion of dMDSCs at the maternal-fetal interface could upregulate the cytotoxicity of dNK cells, leading to pregnancy failures 29 . Human dNK cells are account for about 70% of all decidual immune cells and highly express IL-10 and TGF-β to maintain maternal-fetal immune tolerance and promote fetal development 34 .…”
Section: Discussionmentioning
confidence: 99%
“…LILRB4 is a central inhibitory receptor for uterine dendritic cells (uDCs) and decidual myeloid-derived suppressor cells (dMDSCs), and it plays an important immunomodulatory role at the maternal-fetal interface, thereby ensuring that the process of pregnancy proceeds normally [38,101]. HLA-G is a non-classical MHC class I molecule that is selectively and highly expressed in extrachorionic trophoblast cells invading the uterine metaphysis [102].…”
Section: Lilrb4 and Maternal-fetal Immune Tolerancementioning
confidence: 99%